Research status and trends of Library and Information Science in Taiwan, 2001–2010 / Wen-Yau Cathy Lin and Ka Meng Lio - Wen-Yau, Cathy Lin; Ka, Meng Lio (2011)
The aim of this study is to determine how Library and Information Science (LIS) research in Taiwan has changed between 2001 and 2010. The major research questions are about the research status and trends of LIS in Taiwan, how Taiwanese government support to the field, and how is the collaborative authorship of journal articles in LIS in Taiwan. The bibliometrics and content analysis methods were conducted to analyze 2,458 journal articles, 983 theses, and 179 research projects between 2001 and 2010. The results show that with respect to journal articles, LIS and technology and book, documentation, and archive were the most popular topics. For thesis, the well-received topics were LIS and technology, user services, and LIS theory and foundation, which accounted for more than 65% of the graduate theses. The same is true for research projects, with the three subjects having a ratio of more than 70%. In the government-sponsored research projects, the average amount of funding obtained had no significant differences or tendencies for various subjects over the years. In the authorship of journal articles, 66.64% of the articles in key LIS scholarly journals in Taiwan between 2001 and 2010 were conducted by individual researchers